Training on How to Optimize Product Quality to Increase Purchasing Decisions - Nasution, Muhammad Syukri Albani; Maidalena, Maidalena; Alvin Adriansyah, Ahmad; Hapsah, Zahrani Fatni (Universitas Islam Negeri Sumatera Utara, 2024)
This study aims to conduct training to improve product quality on consumer purchasing decisions for MR D.I.Y. products. The method used involved training with MR D.I.Y employee and the branch manager of MR D.I.Y. on Jalan Pancing. The results indicate that inadequate product quality negatively impacts consumer interest. Consumers tend to feel hesitant about products that do not meet their expectations, which affects brand loyalty. Therefore, it is crucial for MR D.I.Y. to enhance quality control standards and ensure that every product sold undergoes a stringent verification process. By focusing on improving product quality, MR D.I.Y. can strengthen its market position and build positive long-term relationships with its consumers. This research provides practical implications for management to pay more attention to product quality in their marketing strategies.